The Call of the Wild - Paiva, Luke Daniel; London, Jack, 1876-1916.; Horsepool, Adam, 1992- (Oakville, ON : Flowerpot Press, 2021)
"Bucks life as a beloved farm dog changes forever when he is stolen away from his home and taken to the bitter cold of the Yukon. Buck faces many challenges as he is trained to become a sled dog until he finds himself in the hands of John Thornton who helps him ultimately discover where he truly belongs--in the wild. This adapted and condensed fully illustrated version of the tale by Jack London will introduce young readers to the beloved characters from the original and give them a taste of the adventure-filled classic"--Amazon.
Keywords: Dogs -- Juvenile fiction; Sled dogs -- Juvenile fiction; Feral dogs -- Juvenile fiction